A Framework for QoS-aware Class Mapping in Multi-domain SDN - Ali, Jehad; Roh, Byeong Hee (2019 IEEE 10th Annual Information Technology, Electronics and Mobile Communication Conference, IEMCON 2019, 2019)
The Software Defined Networks (SDN) have revolutionized the future Internet technologies through centralized management. Though, the achievements of SDN in the context of centralized management and programmability of networks are numerous. However, its applications for end-to-end (E2E) service delivery in the heterogeneous networks has several challenges. The domains in the heterogeneous networks need collaboration for E2E quality of service guarantee. In this paper we propose a framework based on SDN for E2E service delivery and mapping of service classes. We check the E2E service delivery for various metrics such as delay and jitter. The results of the proposed framework are compared with existing techniques for meeting the E2E QoS requirements of the applications. The results show that the proposed framework not only guarantee the E2E QoS of different applications but also ensures the interoperability among multiple domains.
Keywords: Centralized management; Delay and jitter; Future internet; ITS applications; Multiple domains; Programmability; Quality of service guarantees; Service delivery; heterogeneous networks; mapping; quality of service; service delivery; software defined networking